Pengontrol Suhu Ruangan menggunakan Metode PID - Ramadan Firdaus (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Abstract - Today's automatic control system provides many benefits for humans. Apart from being able to increase work time, automatic control can also reduce human errors and increase work effectiveness. One application of automatic control is controlling temperature with the aim of obtaining the desired temperature in a relatively short time and can maintain the temperature in a stable condition. The temperature control system can be applied using the Arduino and LabVIEW boards. In this temperature control system one LM35 temperature sensor is used. The temperature sensor is placed in a position that is adjusted to the inside of the plant to find the temperature transfer that occurs in the plant. Data from the sensor then goes to the Arduino board, which in this control system uses data as an acquisition. To maintain the temperature inside the factory, use a ventilation fan to lower the temperature if the temperature inside the plant exceeds the set point. To control the fan used this controls the PID which is implemented through LabVIEW. In addition to implementing the PID control, LabView is used as an interface to find out the actual temperature of the plant RPM speed of the fan used and filling in the PID parameters. In the PID approval three parameters can be obtained with Ziegler-Nichols penalties. The results of the study show that the plant response is continuous oscillation and can be overcome by using Ziegler-Nichols continuous oscillation punishment. By using LabVIEW PID and punishment parameters using the Ziegler-Nichols method, for a set point temperature of 28oC the plant response is (28 Â± 0.5) oC. In other words controlling temperature using the PID control and the Ziegler-Nichols method have errors below 2% indicating that the temperature control system is feasible to use. Keyword : Temperature, PID Control, LabVIEW, Arduino board, Ziegler-Nichols.